Diagnostic imaging and therapeutic application of nanoparticles targeting the liver. Issue 6 (14th February 2015) - Wang, Haolu; Thorling, Camilla A.; Liang, Xiaowen; Bridle, Kim R.; Grice, Jeffrey E.; Zhu, Yian; Crawford, Darrell H. G.; Xu, Zhi Ping; Liu, Xin; Roberts, Michael S.
<x xml:space="preserve">Abstract</x> This review summarizes research progress focusing on nanoparticles targeting the liver for both diagnostic and therapeutic purposes at the cellular level.